Vibrant Soundbridge implantation via the third window in two Chinese patients with severe bilateral congenital aural atresia. (January 2014) - Yang, Shi-Ming; Zou, Yi-Hui; Li, Jia-Nan; Jiao, Qing-Shan; Yi, Hai-Jin; Han, Dong-Yi
Abstract Conclusion: In patients with undeveloped vestibular/oval windows and inaccessible round windows, Vibrant Soundbridge (VSB) implantation performed by placing the transducer into a reconstructed window on the inner tympanum wall demonstrated significant improvement in hearing and verbal communication ability. Objective: To report our surgical experience with new placement of the VSB in pediatric patients with undeveloped vestibular windows, inaccessible round windows, and severe bilateral congenital aural atresia (CAA). Methods: In two patients with bilateral CAA selected for middle ear implantation, CT scans revealed severe middle ear malformation including inaccessible round windows, absence of vestibular/oval windows, and abnormal facial nerve anatomy. The transducer of the VSB was implanted into a 'window' drilled at the inner tympanum wall in both patients. Results: The surgery was successful. Pure-tone air conduction thresholds across the frequencies of 0.25–8 Hz were improved by 35 dB (preoperation, 69.2 dB; postactivation, 34 dB) in patient 1 and 46.6 dB (preoperation, 75.8 dB; postactivation, 24.2 dB) in patient 2. Normal hearing thresholds were achieved in the range of 1–8 kHz in both patients. A sentence recognition rate of up to 100% (65 dB SPL in a quiet room) was attained by both patients after surgery and VSB activation at 3 months postoperatively.